The impact of laser radiation frequency on the formation of the main characteristics of ions in a mono-element laser plasma - Japakov Azamat I.; Bedilov Ravshan M.; Kamalova Jamilya O.; Davletov Ikram Y.; Matnazarov Anvar R. (EPJ Web of Conferences)
The purpose of these studies is to study the patterns of development of the characteristics of multiply charged ions in the plasma generated during the interaction of laser radiation with a target operating in the frequency mode. The characteristics of multiply charged ions in monoelement aluminum plasma were studied using laser time of flight mass spectrometers. By changing the laser radiation power in the range from 0.1 to 100 GW/sm2 and different pulse repetition frequencies (1, 3, 5, 10, and 12 Hz), spectra of charged ions of the plasma formed in each case were obtained.